Measurement of spiral artery jets: general principles and differences observed in small-for-gestational-age pregnancies. - Collins, S; Birks, J; Stevenson, G; Papageorghiou, A; Noble, J; Impey, L (2012)
OBJECTIVE: To investigate whether the jets of blood from the mouths of the spiral arteries could be measured reliably, as well as their relationship with the uterine artery (UtA) and any differences in small-for-gestational-age (SGA) pregnancies. METHODS: Participants underwent serial ultrasound scans, from 11 weeks' gestation. Pulsatility index (PI) and resistance index (RI) of jets into the intervillous space (IVS) and UtA were recorded at every visit. Intra- and interobserver variability studies were performed. Customized birth weight centiles were calculated and SGA was defined as < 10(th) centile. Linear mixed model analysis was used to allow for the longitudinal nature of the data. RESULTS: Sixty-six women were recruited; 58 remained normotensive and delivered at term. Of these, six women delivered SGA newborns and 52 delivered appropriate-for-gestational-age newborns. All had pulsatile jets until 20 weeks' gestation. The PI and RI of the jets decreased with advancing gestation, following a trend similar to that of the UtAs. There was no correlation between the jets and UtA waveforms when gestational age was controlled for. For intraobserver variability the intraclass correlation coefficient was 0.9. The interobserver study showed no significant difference between the observers. Mixed model analysis demonstrated that PI and RI of jets were different in SGA pregnancies (P < 0.06). This difference was not seen for the UtAs (P = 0.8). CONCLUSION: This technique enables examination of characteristics of the jets of blood flowing from spiral arteries into the IVS. It is both precise and reproducible, with biologically plausible results. Further work is required to assess differences in pregnancies with adverse outcomes.